2023
DOI: 10.1126/sciimmunol.adf2248
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor Mef2d regulates B:T synapse–dependent GC-T FH differentiation and IL-21–mediated humoral immunity

Abstract: Communication between CD4 T cells and cognate B cells is key for the former to fully mature into germinal center–T follicular helper (GC-T FH ) cells and for the latter to mount a CD4 T cell–dependent humoral immune response. Although this interaction occurs in a B:T synapse–dependent manner, how CD4 T cells transcriptionally regulate B:T synapse formation remains largely unknown. Here, we report that Mef2d, an isoform of the myocyte enhancer factor 2 (Mef2) transcription factor family,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 81 publications
1
2
0
Order By: Relevance
“…MEF2D mRNA expression inversely correlates with TFH populations, autoantibodies, and SLEDAI scores in SLE. 24 Our finding that SAP levels are increased in the circulation of SLE T cells, predominantly TFH and TPH cells, further supports the immunopathogenic role of SLAM-SAP signaling in SLE.…”
Section: Discussionsupporting
confidence: 74%
“…MEF2D mRNA expression inversely correlates with TFH populations, autoantibodies, and SLEDAI scores in SLE. 24 Our finding that SAP levels are increased in the circulation of SLE T cells, predominantly TFH and TPH cells, further supports the immunopathogenic role of SLAM-SAP signaling in SLE.…”
Section: Discussionsupporting
confidence: 74%
“…Similarly, repression of SAP gene transcription by a transcription factor myocyte enhancer factor 2 (Mef2d) has been shown to inhibit SAP-dependent T-B synapse formation and prevent antigen-specific CD4 T cells from differentiation into germinal center TFH cells. MEF2D mRNA expression inversely correlates with TFH populations, autoantibodies, and SLEDAI scores in SLE ( 26 ). Our finding that SAP levels are increased in the circulation of SLE T cells, predominantly TFH and TPH cells, further supports the immunopathogenic role of SLAM-SAP signaling in SLE.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent studies have shown that Mef2d functions as a transcriptional repressor of the Il21 gene, influencing IL-21 production through DNA binding. Mef2d binds to potential Mef2d binding sites in the Il21 gene, demonstrated by luciferase assays, and introducing Mef2d into CD4 T cells from naive mice markedly decreases IL-21 production ( 46 ). Overall, the regulation of IL-21 production in Tfh cells involves a complex network of TFs responding to various extracellular signals.…”
Section: Cytokines Produced By Tfh and Their Regulationmentioning
confidence: 99%